A Project study on the distribution transformers of Philippine Electric Corporation - Bondoc, Odilon; Collera Annabelle; Han, Tai-sook.; Ibana, Enrico; Pimentel, Bernadette; Travina, Uni. (Diliman, Quezon City College of Engineering, 1981)
The production system is one of the major components that determine the life of an industrial institution. Without its due support, the company would be unable to fulfill its commitments which may mean money to the customer. To take it extremely, this may even lead to the loss of clients. What happens then to a business venture without customers? Moreover, for a company to fulfill its objectives, i.e, the maximization of costs, control over the production system should exist. Efficiency of all goings-on should be optimal since the bulk of expenses lies here. This is the field of our study -- the Productions System of the Philippine Electric Corporation with concentration on its forecasting activities and capacity planning. This project site has been chosen since it more or less exemplifies a concrete model of the theories learned in class. To acquaint the reader of our paper, we have started with the introduction by stating the objectives of the study, giving a background of the company, and some information on the product concerned which is the Distribution Transformer. The major areas of consideration were classified as the forecasting system, capacity planning, the distribution transformers and the non-Meralco component of the market. for a greater interaction among the people involved in Production Planning and Control, special job purposes duties and responsibilities are mentioned with due elaboration. The information flow process serves as a guide in the relationships among the departments involved. To understand better the source of the problem, the present forecasting system and the production cycle and process operations are discussed in detail. To give an overview of capacity planning, the plant layout and time standards are given specific sections in the outline of our research. The second part consists of the presentation of the problem and other related factors, the proposed systems with detailed explanations, and the analyses and recommendations. An appendix of graphs is provided at the end of this paper to illustrate the suggested programmed system of forecasting using historical sales. Documented forms used in the information process are also attached herewith so that the reader can visualize clearly what is referred to in information flow process. Also, a sample of a filled-up capacity planning sheet is added to help the reader in understanding the procedure of allocating the labor force. Other recommended forms are likewise presented here.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Philippine Electric Corporation; Electric utilities; Production engineering